1996
DOI: 10.1074/jbc.271.36.22271
|View full text |Cite
|
Sign up to set email alerts
|

The CCAAT-binding Proteins CP1 and NF-I Cooperate with ATF-2 in the Transcription of the Fibronectin Gene

Abstract: We have previously proposed a molecular interaction between the liver factors that bind to the cyclic AMP response element (CRE) and CCAAT sites of the fibronectin (FN) gene based on the following evidence: (i) the close spacing of 20 base pairs between CRE and CCAAT elements is conserved in the FN genes from rats, mice, and humans; (ii) footprinting competitions showed that CRE oligonucleotides are able to detach both liver factors; (iii) CCAAT binding and transcriptional activity of liver extracts are reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 44 publications
(36 reference statements)
2
37
0
Order By: Relevance
“…Although these two proteins can coimmunoprecipitate (46), we have no evidence that ATF2 and ATF4 may form a dimer that binds the AARE sequence, but they could be included in a larger regulatory protein complex. For example, it has been shown that ATF2 interacts with at least two transcriptions factors (CP1 and NF1) in a protein complex that regulates transcription of the fibronectin gene (47). We have also shown that, beside the GCN2 pathway that leads to ATF4 induction, other amino acid-dependent signals are required to phosphorylate ATF2 and to maximally activate the AARE-dependent transcription.…”
Section: Discussionmentioning
confidence: 78%
“…Although these two proteins can coimmunoprecipitate (46), we have no evidence that ATF2 and ATF4 may form a dimer that binds the AARE sequence, but they could be included in a larger regulatory protein complex. For example, it has been shown that ATF2 interacts with at least two transcriptions factors (CP1 and NF1) in a protein complex that regulates transcription of the fibronectin gene (47). We have also shown that, beside the GCN2 pathway that leads to ATF4 induction, other amino acid-dependent signals are required to phosphorylate ATF2 and to maximally activate the AARE-dependent transcription.…”
Section: Discussionmentioning
confidence: 78%
“…These genes lack any predicted perfect NFI dyad symmetric binding sites. While some mammalian promoters have been shown to contain functional hemi NFI binding sites (a single TTGGC or GCCAA site alone) (Cereghini et al, 1987;BoisJoyeux and Danan, 1994;Alonso et al, 1996;Gao et al, 1996), the absence of high-affinity dyad symmetric NFI binding sites within the myosin and exp-2 genes raises the possibility that they may not be direct targets of NFI.…”
Section: Fig 2 Amentioning
confidence: 99%
“…Cooperativity between the neighbouring CRE and CCAAT sites has been extensively studied in our laboratory [24,25]. Introduction of disruptive point mutations into the CRE and CCAAT sites in the context of the proximal 220 bp reduces transcriptional activity by at least 80% in FN promoter-chloramphenicol acetyl transferase (FN-CAT) constructs transfected in various cell lines of either mesenchymal (NIH 3T3, HT1080) or epithelial (Hep3B, HepG2) origins (C.G.…”
Section: Promoter Sequence Analysismentioning
confidence: 99%